Impact of Disease Severity, Illness Beliefs, and Coping Strategies on Outcomes in Psoriatic Arthritis. Issue 2 (29th December 2017) - Howells, Laura; Chisholm, Anna; Cotterill, Sarah; Chinoy, Hector; Warren, Richard B.; Bundy, Christine
Abstract : Objective: Little is known about how people with psoriatic arthritis (PsA) cope with and manage their condition, but data show that psychological problems are underrecognized and undertreated. The Common Sense Self‐Regulatory Model (CS‐SRM) suggests illness beliefs, mediated by coping, may influence health outcomes. The study aimed to investigate the roles of disease severity, illness beliefs, and coping strategies in predicting depression, anxiety, and quality of life (QoL) in people with PsA. Additionally, we aimed to assess the role of depression and anxiety in predicting QoL. Methods: We conducted a cross‐sectional observational study, where adults with PsA (n = 179) completed validated measures of predictor (illness beliefs, coping strategies, disease severity) and outcome variables (depression, anxiety, QoL) using an online survey distributed via social media. Results: The participants were a community sample of 179 adults with PsA, ages 20 to 72 years (77.1% female). After controlling for disease severity, hierarchical multiple regression models indicated that more negative beliefs about consequences and behavioral disengagement as a coping method predicted levels of depression, and self‐blame predicted anxiety. Beliefs about consequences and the presence of depression predicted quality of life scores after controlling for disease severity. Conclusion: This study offers support for the use of the CS‐SRM in explaining variation on psychological outcomes in individuals with PsA. The illness beliefs and coping strategies identified as predictors in this article are potential targets for interventions addressing PsA‐related distress and QoL.